2008
DOI: 10.1128/mcb.01332-07
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Heart Development and Lung Remodeling in Mice Lacking the Hypoxia-Inducible Factor-Related Basic Helix-Loop-Helix PAS Protein NEPAS

Abstract: Hypoxia-inducible factors (HIFs) are crucial for oxygen homeostasis during both embryonic development and postnatal life. Here we show that a novel HIF family basic helix-loop-helix (bHLH) PAS (Per-Arnt-Sim) protein, which is expressed predominantly during embryonic and neonatal stages and thereby designated NEPAS (neonatal and embryonic PAS), acts as a negative regulator of HIF-mediated gene expression. NEPAS mRNA is derived from the HIF-3␣ gene by alternative splicing, replacing the first exon of HIF-3␣ with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
150
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(164 citation statements)
references
References 36 publications
13
150
0
1
Order By: Relevance
“…In general, HIFs are vital to proper development and deletion of the HIF-1α gene results in prenatal death. HIFs are crucial for oxygen homeostasis during both embryonic development and postnatal life (Yamashita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, HIFs are vital to proper development and deletion of the HIF-1α gene results in prenatal death. HIFs are crucial for oxygen homeostasis during both embryonic development and postnatal life (Yamashita et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis by RT-PCR revealed that HIF-3α mRNA is broadly expressed in various tissues of the mouse during embryonic and neonatal stages and that HIF-3α expression gradually decreases at 15 days postnatal (Yamashita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, alternative splicing of the mouse HIF-3 locus generates NEPAS and IPAS mRNA species which appear to be tissue-specific and strictly regulated by hypoxia, defining a novel mechanism of hypoxia-dependent regulation of gene expression 69,73 . In tumors this mechanism is an attractive means to target HIF signaling.…”
Section: Pre-mrna Splicingmentioning
confidence: 99%
“…Moreover, the expression of IPAS in the cornea correlates with low vascular endothelial growth factor (VEGF) gene expression under hypoxic conditions 68 . Recently in mice, another hypoxia-inducable negative regulator NEPAS (neonatal and embryonic PAS protein) was found 69 . Its mRNA, as in the IPAS case, derives from the HIF-3 gene by alternative splicing, where the first exon of HIF-3 is replaced with the IPAS first exon.…”
Section: Pre-mrna Splicingmentioning
confidence: 99%
See 1 more Smart Citation